Ragam Jenis Semut (Hymenoptera: Formicidae) di Lahan Ga mbut Alami dan Perkebunan Sawit di Kecamatan Sungai Ambawang Kabupaten Kubu Raya - Ari Hepi Yanti, Dita Meilina, Tri Rima Setyawati (Universitas Tanjungpura, 2017)
Ants are one of bioindicators in peatland ecosystems. Peatlands are changing from natural conditions due to the oil palm plantations. This study aims to determine the diversity of ants in natural peatland and oil palm plantation at Sungai Ambawang District Kubu Raya. The research was located in 3 different sites, such as natural peatland, cleared peatland and the peatland that had been converted to oil palm plantation. Ants were collected by pit-fall trap, soil and leaf litter sieving, and bait trap method. There were 7 genera from 3 subfamilies (Dolichoderinae, Formicinae, and Myrmicinae) of ants found in this research. Dolichoderinae consisted of the genera Loweriella and Tapinoma, Formicinae consisted of Camponotus and Echinopla, while Myrmicinae consisted of Acanthomyrmex, Crematogaster, and Rhoptromyrmex. The Shannon diversity index (H’) of natural peatland was higher (H’ 1.12) than cleared peatland (H’ 0.00) and converted peatland (H’ 0.69). This indicates that the conversion of peatlands decreased ant species diversity.